MODERN POSSIBILITIES OF DIAGNOSTICS AND TREATMENT OF PATIENTS WITH RETROPERITONEAL TUMORS - E. A. Suleimanov; A. D. Kaprin; A. A. Кostin; L. I. Moskvicheva (Сибирский онкологический журнал, 2017)
The review deals with the evaluation of options antitumor treatment of retroperitoneal tumors, the use of intraoperative methods of the local adjuvant cancer treatment in the combined treatment of patients with resectable retroperitoneal tumors. Presents data of the occurrence of this pathology among all tumors and soft tissue sarcomas, described the risks of recurrence and metastatic potential of retroperitoneal tumors. The peculiarities of surgical interventions regarding recurrence non-organ retroperitoneal tumors, associated with topographic and anatomical features of the retroperitoneal space, multicentricity the rudiments of the tumor, aggressive invasive growth. The possibilities of radiation therapy of primary and recurrent tumors of this localization.